2007
DOI: 10.1152/ajprenal.00416.2006
|View full text |Cite
|
Sign up to set email alerts
|

Canonical WNT signaling during kidney development

Abstract: The canonical WNT signaling pathway plays a crucial role in patterning of the embryo during development, but little is known about the specific developmental events which are under WNT control. To understand more about how the WNT pathway orchestrates mammalian organogenesis, we studied the canonical ␤-catenin-mediated WNT signaling pathway in kidneys of mice bearing a ␤-catenin-responsive TCF/␤Gal reporter transgene. In metanephric kidney, intense canonical WNT signaling was evident in epithelia of the branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
133
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(146 citation statements)
references
References 33 publications
13
133
0
Order By: Relevance
“…13 This is strikingly similar to the WNT4 knockout mouse model that showed defective mesenchymal-epithelial transition (MET), lack of nephron formation, and development of renal hypodysplasia, 14,15 in addition to defective sexual differentiation exclusive to the female model. Supporting our findings, the male mouse model showed only isolated RHD, similar to both affected males described herein.…”
supporting
confidence: 57%
“…13 This is strikingly similar to the WNT4 knockout mouse model that showed defective mesenchymal-epithelial transition (MET), lack of nephron formation, and development of renal hypodysplasia, 14,15 in addition to defective sexual differentiation exclusive to the female model. Supporting our findings, the male mouse model showed only isolated RHD, similar to both affected males described herein.…”
supporting
confidence: 57%
“…[27][28][29] Wnt9b, Wnt7b, and Wnt4 are indispensable in the inductive signals leading to the epithelia that form the nephron, 30,31 and they are reactivated during renal repair and in renal fibrosis. [32][33][34] In renal repair, Wnt4 stimulation contributes to cellular proliferation and epithelial reconstitution.…”
Section: Discussionmentioning
confidence: 99%
“…b-Catenin reporter genes in transgenic mice have shown strong activity in the tips and stalks of the branching ureteric bud. 12,13 Using Hoxb7Cre mice to remove b-catenin from the developing ureteric bud, it was found that b-catenin is required for ureteric branching. 14,15 Finally, Wnt7b/b-catenin signaling has been shown to direct collecting duct growth and extension of the loop of Henle in the medullary zone.…”
mentioning
confidence: 99%